Creative life-orientation as a personal phenomenon (monograph) [Жизнесозидающая креативность как личностный феномен (монография)] (in Russian) - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна (Saarbrucken, Germany: LAP LAMBERT Academic Publishing, 2017)
In this study, in order to distinguish between the concepts of “creativity” and "internal life-creating direction", a new concept of “creative life-orientation” (CLO) is introduced, to which is given its own psychological essence and interpretation. Thus, each phenomenon (“creativity” and “CLO”) gets its own interpretation and scientific justification, reflects its own psychological essence, determines its own psychic substance, has a personal concept and mechanism, and thus it is possible to avoid their equivalency. It is shown that CLO shows its humanistic essence and sanogenic qualities only on the basis of spirituality, which a priori includes intrapersonal and interpersonal aspects (Harmony-Love and Dialogue-Consensus): only in this case, CLO is a life-creating internal recreational orientation. Otherwise, the life orientation of the personality mutates (transforming into a form of primitive self-assertion under the pressure of narrow-personality priorities and ambitions), which leads to the emergence of the “anti-creativity” syndrome. An interdisciplinary system-humanistic approach to the study of CLO has been developed, which allowed to reveal its psychological mechanism (on the basis of the concept developed by the author and the conceptual model of CLO). It is shown that motives and emotions are connected in a single complex. Synergo-empathic substance produces an attractive-empathic force, which contributes to the unity of intentions, emotions and aims. Simultaneously, the work of various subsystems of the body is synchronized, psycho-physiological self-regulation takes place, and spirituality is enriched. Attraction-empathy factor activates the motivational-incentive block of CLO, which stimulates cognitive-motor activity and ensures the achievement of common goals. A functional and operational model of CLO has been created, on the basis of which it has been established that: a) both spirituality and CLO are not only a prerequisite for the process of person's self-stabilization / self-actualization, but also a goal which he achieves; b) spirituality and CLO are manifested, then acting in a synergistic unity: firstly, they mutually stimulate each another, and secondly, they represent a single comprehensive indicator of health promotion; c) CLO has a dualistic character: at the initial stage it appears as a condition for the development of spirituality, creating a life plan, stabilizing health and building a positive existence algorithm, and at the next stage it acts as a result (a person accepts it as the main further mode in life). It is established that personality evolution and CLO are interdependent (if necessary, a person’s internal reserves can be strengthened using ancient Oriental self-healing techniques, the purpose of which is to replenish the energy reserve and normalize psychosomatics for further spiritual and intellectual development). The repetition of this cycle stabilizes CLO: the process of its opening becomes a permanent determinate one and spontaneously manifests itself in other areas of vital activity. A new concept – namely, “self-organizing psychological system”, which characterizes a social group in the interaction of subjects of the educational and professional sphere – has been introduced. The following is empirically stated: 1) an increase in the index of psychosomatic health is reflected in the general mode of existence, that indicates the ordering of various areas of the mental - emotional, motivational, behavioral and cognitive; 2) the process of creative self-disclosure a priori has stress-preventive and health-preserving effects, which is an important recreational factor: in a person who is in a creative state, the cognitive, motor, motivational-volitional and psycho-physiological spheres of activity are synchronized, emotional-perceptual protection from negative stimuli is created, the ability to emotionally-heuristic self-stimulation and rational self-regulation arises; 3) since CLO is composed of the spiritual, genetic and intellectual resources of the individual, so CLO figures as the organizer of cognitive-emotional experience and effective self-realization. An innovative technology of linguistic education has been developed. The student period is characterized as an important point for self-determination and formation of a life position, which was empirically confirmed.
Keywords: creative life-orientation; spirituality; need-motivational intentions; emotions; positive social environment; health promotion; ancient Oriental self-healing techniques; normalization of psychosomatics